What They Do Not Talk about When They Talk about Radicalism: (A Corpus-assisted Discourse Analysis on Islamic News Portals in Indonesia) - Oemar Madri Bafadhal; Nurly Meilinda; Krisna Murti; Anang Dwi Santoso (MediaTor (Jurnal Komunikasi), 2020)
The lack of a clear definition of radicalism leads Islamic organisations to feel entitled to interpret it. It results in contention for the meaning of radicalism and forms a different reality for each reader. By taking a case study on two spectra of Islamic organisations, moderate Islamic organisation (NU Online) and Islamic extremist organisation (Portal Islam), this study aims to understand the construction of radicalism in two Islamic news portals. We utilised a dataset of news about radicalism from September 2018-2019 and analysed it using a combination of corpus linguistic (CL) and critical discourse analysis (CDA). While CL helped to reveal emerging discourses, CDA intended to observe the patterns and relate them into socio-political contexts critically. The results indicate that each site was blurring the information function of news portals into a propaganda function. They also generate fragmented knowledge, which leads to a misrepresentation of paradigm towards radicalism. This leads to discriminatory actions against other groups. The meaning of radicalism in the media may encourage group dichotomy, which is counterproductive to countering terrorism in Indonesia. This study contributes to a comprehension of the terrorism phenomenon by providing a closer view of how moderate and extreme Islamic organisations interpret radicalism.